The Potential of Rhizophagus intraradices, Bacillus thuringiensis Bt BMKP and Silica for Anthracnose Disease Control in Shallot - Amallia, Rizky; Suryanti, Suryanti; Joko, Tri (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Anthracnose caused by Colletotrichum gloeosporioides is a prevalent disease that poses a significant threat to shallot production in Indonesia. To mitigate this issue, the use of biological agents presents an alternative for disease control, reducing the inherent risks associated with the use of chemical pesticides. Therefore, this study aimed to determine the potentiality and mechanism of the biological agents (Rhizophagus intraradices and Bacillus thuringiensis) combined with silica. These agents were evaluated both individually and in combination to suppress the development of anthracnose in Tajuk variety shallot. The study was conducted in the laboratory and greenhouse, arranged in a completely randomized design with six treatments and three replications. The ability to suppress pathogenic fungi was determined based on in vitro antagonism tests of B. thuringiensis, disease severity, area under disease progress curve (AUDPC), plant height, number of leaves, number of tillers and the percentage of mycorrhizal fungal infections. Furthermore, the mycorrhizal infection on plant roots was observed using staining methods. The results showed that the Bt BMKP isolate was included in the B. thuringiensis strain RC9 group with the capacity to inhibit C. gloeosporioides in vitro by 18.88%. The combination treatment of R. intraradices, B. thuringiensis and silica reduced infection from anthracnose by 15.52% compared with control. These three treatments also significantly increased the agronomic performance of shallot up to six weeks after planting compared to control and other treatments.